Folding of aromatic polyamides into a rare intrachain β-sheet type structure and further reinforcement of the secondary structure through host–guest interactions - Samanta, Subhendu; Mallick, Dibyendu; Roy, Raj Kumar (Royal Society of Chemistry, 2022)
Aromatic oligoamides have been shown to adopt various secondary structures, such as helical structures, linear strands, etc., but synthetic β-sheet structures are not well known. Here we demonstrate the intrachain β-sheet like folded structure of aromatic polyamides. Precise placement of H-bonding and π-stacking motifs along the polymer chain was necessary for the folding process. The control polymer without intramolecular H-bonding motifs assumed a random-coil structure. Unfolding of the polymer was observed at higher temperatures; however, the presence of π-surface containing guest molecules improved the thermal stability of the folded structure through co-facial host–guest π-stacking interactions. The possible applications of these molecules as through-space electron-conducting materials, organocatalysts, etc. can be envisaged.
Only IISERM authors are available in the record
Keywords: Aromatic polyamides; Intrachain β-sheet